CORRELATION OF BONE MARROW PLASMACYTOSIS WITH ABNORMAL BLEEDING PATTERN AND CONGO RED STAINING - Akhil (Journal of Biomedical and Pharmaceutical Research, 2020)
Background: The plasma cell is round or oval in shape, the cytoplasm is abundant and intensely basophilic, usually deep blue. The nucleus is small in relation to the cell size, round or oval, eccentrically placed, and contains dense masses of chromatin arranged in pyramidal blocks against the nuclear membrane, giving the characteristic "cartwheel" appearance. Plasma cell dyscrasias form a heterogeneous group of diseases characterized by expansion of the number of monoclonal bone marrow plasma cells that produce monoclonal immunoglobulins. Material and Methods: A thorough clinical evaluation of the patients with bone marrow plasmacytosis coming to SS Hospital, BHU from October 2017 to May 2019 was done, including history taking, physical examination and relevant investigations. Patients not giving consent for participation in the study were excluded. Results: The mean prothrombin time among 42 patients was 15.3 seconds. Prothrombin time was prolonged in 17 patients (40.5%). The mean APTT among 42 patients was 32.1 seconds. APTT was prolonged in 19 patients (45.2%). Isolated prolongation of PT was observed in 3 patients (7.1%) and isolated prolongation of APTT was observed in 3 patients (7.1%). Platelet aggregation studies were performed in 33 patients. Platelet aggregation with adrenaline was abnormal in 11 patients (33.3%) and aggregation with ADP was abnormal in 18 patients (54.5%). Conclusion: Generalised weakness and easy fatiguability was the commonest presenting complaint and bone pain was relatively less common than in other studies. Bone lesions were also relatively less common in our study as compared with other studies. Active bleeding was observed in 3 patients with 2 of them having epistaxis and one with per rectal bleed. Coagulation tests were abnormal in many cases of plasma cell dyscrasias but most patients were asymptomatic. Abdominal /gluteal fat pad aspiration and Congo red staining showed faint positivity in only one patient. Keywords: Bone marrow, Plasmacytosis, Congo red staining, Electrophoresis, PT and APTT